Providing remote school-based professional support to teachers during school closures caused by the COVID-19 pandemic. (2nd January 2021) - Moorhouse, Benjamin Luke; Lee, Jonathan; Herd, Simon
ABSTRACT: This small-scale exploratory study explores the practices and experiences of two experienced Hong Kong Education Bureau Advisory Teachers (ATs) engaged in school-based professional support (SBPS) of teachers during school closure caused the COVID-19 pandemic. It documents the ATs usual practices, conditions for effective SBPS, the effect the pandemic had on their practices, and the specific support they provided remotely during the pandemic. Key findings indicate that effective SBPS requires clear role expectations, a collaborative support approach, building strong relationships and durability. The SBPS model is resilient and allows ATs and teachers to adjust to the evolving situation. ATs have continued to provide support throughout the school closures, something that would not have been possible without the existing SBPS model, relationship cultivated over an extended period of support and available technology. The authors recommend that Education Bureaus explore SBPS as a way to continue supporting teachers during school closures.